Prediksi Financial Distress menggunakan model Z-Score pada bank yang terdaftar di Bursa Efek Indonesia - Hendi Hendi; Kellys Kellys (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Banking companies in a country are the center of a country's financial turnover and have an important role in the economy of a country. This study aims to determine the factors that affect financial distress in banks listed on the Indonesia Stock Exchange using the Z-Score model. High financial distress indicates that companies often experience difficulties in financial turnover. The conclusion from this research is that ETA, NPL and Size have a significant positive effect on financial distress. LLP has a significant negative effect on financial distress. The CAR, CIR, ROA, LADF, Deposit and Auditor Type variables do not have a significant effect on financial distress.